Influence of Gender Inequality in Employment and Inequal Employment Opportunities on Women’s participation in the Saudi Labor Market during (2010- 2020) - Alfarran, Abeer Kamel (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed at identify the influence of gender inequality in employment and inequal employment opportunities on women’s participation in the Saudi labor market. The importance of the study lies in addressing the scientific gap due to the lack of previous scientific studies, which dealt with gender inequality and the extent of their impact on women’s participation in the Saudi labor market. Moreover, to documenting and evaluating the legal reforms and regulations of the Saudi labor market that aimed to reduce the gender inequality in employment and inequal employment opportunities. The researcher used the relational research method based on hypotheses, which depends on an in-depth review and compilation of evidence from previous secondary sources during (2010-2020), related to the study problem. For data analysis, the researcher used (EViews software), and performed statistical treatments using the Victor autoregressive (VAR) model. The study found that gender inequality in employment and equal employment opportunities cause about 30% of the low participation of women in the Saudi labor market. The study recommended passing clear, explicit and binding legislation related to both employment and job opportunities on an equal footing for both genders.